Resumption of Urban Brownfields - Mohammadreza Pourmohammadi; Aliakbar Taghipour (نشریه جغرافیا و برنامه‌ریزی, 2013)
Land is a key factor for all human activities such as providing housing, services and urban infrastructure. Efficient and optimal use of land resources is among very important responsibilities of urban planning and managers. This issue most of time is being neglected or little attention is paid to it especially in less developed countries. While in some areas considerable parcels of land for legal, economic or because of environmental reasons are left unused, intensive constructions are carried out in other parts. Attempts are made in this article to highlight the importance and of resumption of unused or misused urban lands and brought toward appropriate suggestions to improve the difficulties and problems of land availability.